Ukrainian nationalism and Viktor Polishchuk as its historian - Grott, Bogumił (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article deals with the problem of Ukrainian nationalism and its significance in Polish-Ukrainian relations. It considers the role of the Ukrainian Nationalist Organization (OUN) established in 1929, and its militia, the Ukrainian Insurgent Army (UPA), and the genocide committed by these organizations and the Ukrainian population supporting them during the World War II on Poles living in the south-eastern voivodeships of the Second Polish Republic.
Keywords: Ukrainian nationalism; works by Associate Professor Viktor Polishchuk; Bishop Grzegorz Khomyshyn`s opinions